IMPLEMENTASI PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN (PAKEM) BERBASIS PENDIDIKAN KARAKTER DALAM MENINGKATKAN MUTU PEMBELAJARAN PAI - Zaedun Naim (STAI Ma'had Aly Al-Hikam Malang, 2013)
The concept of character education is suited to be applied in formal education (school), because the character education is implant the values of character to the school community which includes the component of knowledge, the awareness or the willingness, and the actions to implement those values. The implant of character values to the students can be conducted , through learning, because based on learning activities be sides to make students mastering the competencies (matter) targeted, is also designed to make the students are recognize, aware or care, internalize the values, and make it being their behaviors.